AN ASSESSMENT OF THINKING SKILLS IN ‘ENGLISH SKILLS FOR THE FUTURE’ FOR JUNIOR HIGH SCHOOL GRADE XII - Nangoy, Feren; Liando, Nihta V. F.; Kumayas, Tirza (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
In 2013, Indonesia developed a brand-new scientific-based English instruction curriculum that emphasized the growth of communicative competence. In addition, the curriculum aims to develop students' thinking skills so that they can function as independent, responsible, and critical learners who are able to communicate effectively in English. As a direct consequence of this, authors of textbooks either called for the creation of brand-new textbooks tailored to the new curriculum and its four domains or attempted to adapt existing textbooks to the new curriculum. As a result, numerous books have been written for 7th grade SMP/MTs and 12th grade SMA/SMK/Aliah. The study sought to determine whether textbooks encourage critical thinking and the proportion of various thinking skills. Due to the textbooks as the data source, the current study was classified as a content analysis. Based on the results, it can be seen that the majority of the items are strategically located in L1 (Remember), with two hundred sixty-one questions (67 percent), followed by ninety-two questions (23 percent) in L2 (Understand), twenty-four questions (6 percent) allocated in L3 (Apply), and the remaining nine questions (2 percent) in L4 (Analyze). Consequently, the textbook described the lower order thinking level's prioritization. Although there was not a uniform distribution of each thinking level, the textbook promoted critical thinking in the EFL learning process and encouraged students to investigate their lower thinking level.